Analisis Titik Rawan Kecelakaan di Jalan Kertanegara Kabupaten Malang - Rifky Aldila Primasworo; Andy Kristafi Arifianto (Department of Civil Engineering and Planning, Faculty of Engineering, Sriwijaya University, 2021)
Kertanegara is one of the roads in Malang Regency. The location of Kartanegara Road is considered to be one of the locations prone to accidents due to the lack of traffic infrastructures such as signs and road markings. The road is also an alternative highway that connects Malang Regency to Batu City. The data obtained shows that traffic accidents amounted to 43 of all types of traffic violations from 2016-2018. In 2016, 2017, and 2018, the number of accident victims was 18 accidents, 9 accidents, and 16 accidents. The purpose of this study is to determine the characteristics of Kertanegara road, accident-prone points, and solutions used to reduce the number of accidents. The analytical method used is the analysis of road characteristics, Z-Score, and Cusum analysis. The results obtained that service level of Kertanegara road is 0.61 where the flow is stable, the traffic density is moderate. Based on the analysis of the determination of accident-prone points, the result of Kartanegara road segment, Malang Regency, has a Z-Score for segment I of 0.25 and segment II of 0.17 which is included in the accident-prone criteria because it has a positive Z-Score. Kartanegara Road has also been identified as a black spot because it has a positive cusum value, including the Cusum segment I values of 7.00 and segment II of 13.3. The solution is to provide a traffic sign in the form of a traffic light at the intersection of Police Karangploso road and the intersection of Sentana road, providing management officer traffic flow in Simpang Nuril road and providing warning signs that are prone to accidents and vehicle speed limit at the Crossroads Kauman I and intersection Nuril road.